Mr. and Mrs. Elliott standing outside a house, Ketchikan, Alaska, circa 1929-1930 - Unidentified
Probably Roy and Bessie Elliott (both born around 1893). Roy was a self-employed fisherman. Written on photograph: Mr. and Mrs. Elliott at home PH Coll 1331.17c